2023
DOI: 10.1002/adfm.202309010
|View full text |Cite
|
Sign up to set email alerts
|

Achieving 17.46% Efficiency CsPbI2Br Perovskite Solar Cells via Multifunction Lead Chloride‐Modified ZnO Electron Transporting Layer

Yaru Li,
Yong Zhang,
Peide Zhu
et al.

Abstract: CsPbI2Br perovskite solar cells (PSCs) have garnered significant attention owing to their remarkable thermal stability and desirable bandgap. However, CsPbI2Br‐based devices still face critical challenges, particularly at the interfaces between the active layer and adjacent components. In this study, a multifunctional ZnO composition has developed as the electron transporting layer (ETL) for CsPbI2Br PSCs, enabling simultaneous efficient charge extraction and passivation of buried interface defects in CsPbI2Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…reported that PbCl 2 -modified ZnO can reduce iodine defects and improve the film quality, thereby enhancing electronic extraction. 52 Electrochemical impedance spectroscopy analysis was also conducted to gain additional insights (Fig. S3†).…”
Section: Resultsmentioning
confidence: 99%
“…reported that PbCl 2 -modified ZnO can reduce iodine defects and improve the film quality, thereby enhancing electronic extraction. 52 Electrochemical impedance spectroscopy analysis was also conducted to gain additional insights (Fig. S3†).…”
Section: Resultsmentioning
confidence: 99%
“…然而, 有机无机杂化钙钛矿中的有机阳离 子 如 甲 胺 基 团 或 甲 脒 基 团 (methylamine, MA + ; formamidine, FA + )在高温下极易与氧或水反应, 导致钙钛矿结构最终分解为有机气体和碘化铅 [4] . 为了克服有机阳离子的不稳定性问题, 研究者转 向到耐热的全无机CsPbX 3 (X为Cl, Br, I或混 合 卤 素 )钙 钛 矿 的 研 究 [5][6][7] . 如 混 合 卤 化 物 钙 钛 矿CsPbI 2 Br因其优异的热稳定以及合适的带隙 (1.90 eV), 可作为半透明太阳能电池和叠层电池中 的顶电池而备受关注 [8,9] .…”
Section: 引 言unclassified